Reaching Beyond the Moron : Eugenic Control of Secondary Disability Groups - Bundy, Meghan E. (2009)
While much has been published about the American eugenics movement, few authors have considered the relative status of various disability populations as targets of eugenic control. While many writers focus on persons diagnosed as feeble-minded as the central focus of control, little has been written regarding the status of additional disability groups. This is important since, as described here, a central component of coming to understand past social injustices against marginalized groups and the contemporary relevance of such injustices is gaining an awareness of why specific populations were accepted by control authorities as appropriate or viable targets for control measures